Inherently degradable cross-linked polyesters and polycarbonates: resins to be cheerful. Issue 40 (7th October 2020) - Șucu, Theona; Shaver, Michael P.
Abstract : We summarise the most recent advances in the synthesis and characterisation of degradable thermosetting polyester and polycarbonates, including partially degradable systems derived from itaconic acid and isosorbide. Abstract : Thermosets are an important class of materials that provide excellent temperature and solvent resistance; however, their high dimensional stability precludes degradation or reprocessing. While traditional thermoplastics can be mechanically and chemically recycled, these pathways are often elusive for resins due to their intrinsic structure. The renewed demand for sustainable polymers from public, industry and government stakeholders has increased research into (bio)degradable thermoplastics, but thermosets have often been overlooked. Aliphatic polyesters and polycarbonates are the cornerstone of biodegradable polymers, yet offer an arguably greater potential in thermosets as end-of-life options are more limited for these materials. This review summarises the most recent advances in the synthesis and characterisation of degradable thermosetting polyester and polycarbonate materials, including partially degradable systems derived from renewable resources such as itaconic acid or isosorbide. The review is organised by synthetic methodology including one-pot reactions and multi-step approaches making use of pre-polymers. Photo-cross-linking and high-energy irradiation are also discussed as emerging synthetic strategies.